1981
DOI: 10.1111/j.1398-9995.1981.tb01835.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect in Man of Anti‐Allergic Drugs on the Immediate and Late Phase Cutaneous Allergic Reactions Induced by Anti‐IgE

Abstract: Wheal and flare reactions as well as a late cutaneous allergic reaction (LCAR) were induced by anti-human IgE in healthy subjects. The effect of the beta 2-adrenoceptor stimulant terbutaline, the histamine-1 (H1) receptor blocking agent mepyramine and the synthetic glucocorticoid betamethasone on these reactions was studied. All administrations were given intradermally (i.d.). The immediate reaction to anti-IgE was inhibited by 3 micrograms terbutaline and 30 micrograms mepyramine (P less than 0.01) whereas 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
25
3

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 16 publications
7
25
3
Order By: Relevance
“…This is in harmony with other studies which also report the lack of effect by prednisolone on weal and flare responses elicited by other challenge agents such as compound 48/80 or histamine [11,12]. Since only a limited number of the subjects in the present study exhibited a visual late phase, we cannot deter mine whether the present dose of prednisolone also inhibits the symptomatic expression of a dermal late phase as has been reported previously [13], although there was an inhibition of the local eosinophil influx.…”
Section: Discussioncontrasting
confidence: 42%
“…This is in harmony with other studies which also report the lack of effect by prednisolone on weal and flare responses elicited by other challenge agents such as compound 48/80 or histamine [11,12]. Since only a limited number of the subjects in the present study exhibited a visual late phase, we cannot deter mine whether the present dose of prednisolone also inhibits the symptomatic expression of a dermal late phase as has been reported previously [13], although there was an inhibition of the local eosinophil influx.…”
Section: Discussioncontrasting
confidence: 42%
“…Both studies found increased wheal reactions in the late evening when serum cortisol levels are low. In the majority ofhuman studies, however, pharmacological doses of steroids do not appear to influence immediate mast cell responses (30)(31)(32)(33)(34). A recent study by Vichyanond and Nelson (35) and experiments reported here failed to detect diurnal variation in early phase responses after cutaneous antigen challenge.…”
Section: Discussioncontrasting
confidence: 41%
“…This reaction has been used in humans to evaluate the effects of drugs on IgE-mediated reactions. [10][11][12][13][14][15][16] In dogs, a model of allergic dermatitis has been successfully developed by the use of anti-IgE. 8,9 To our knowledge, such a model of allergic dermatitis in horses has not been developed.…”
Section: Anti-igementioning
confidence: 98%
“…Researchers have effectively developed models of cutaneous allergic inflammation in other species, including dogs 8,9 and humans. [10][11][12][13][14][15][16] Briefly, allergic skin disease is often mediated by type I hypersensitivity reactions. These reactions (immediate and late-phase hypersensitivity) are initiated by antigen exposure.…”
Section: Anti-igementioning
confidence: 99%